Reading skills and text comprehension competences of scholarship students from indigenous Amazonian communities: an Eye Tracking case study - Gabriel Levrini (Universidade Estadual Paulista Júlio de Mesquita Filho, 2020)
The objective of this research is to analyze the reading skills of scholars with eye tracking device from native Amazonian communities contemplated with universities scholarships from the Government of Peru using biometric, linguistic and psychological techniques. Two group of escolar were selected as experiment sample: the first group 48 selected scholarship students from five different Peruvian Amazon public and private universities; and the second group, used as control, contained 46 scholarship student from three different universities based in metropolitan Lima. Literature research explore educational potential in relation to the individual characteristic of reading comprehension skills, which, by definition, is related to learning from text reading.The main research conclusions are: a) on average, scholarship beneficiaries from indigenous communities have a greater fixation duration than recipients from Lima based students' in all the Areas of Interest; b) on average, grantees from Amazon communities had more fixation points in all the areas of interest, which could mean greater difficulty understanding the texts, in some AOI, significant differences were found between the groups; c) grantees from Amazon communities had greater fixation duration and more fixation points, which indicates longer reading time and potential problems in reading comprehension; d) Scholars also showed more difficulty to understanding texts. Nevertheless their proved that their major effort in the reading process also represents a major greater success for them as scholarship members.